Dielectric Control of Motor Fuel Compounding Plants - Sater, Nabil Abdel; Grigorov, Andrey; Neustroieva, Gelena; Bondarenko, Oleksandr; Matukhno, Vasyl; Vavreniuk, Sergii (My University, 2022)
The article proposes the use of operational dielectric control system to increase the efficiency of operation of automatic compounding of motor fuels. These plants are used at oil refining enterprises in Ukraine and are an integral part of the technological chain of the commercial fuels production. It is established that all the main components and additives used for the production of commercial gasoline brands A-92, A-95 and A-98 have higher values (εmix) than straight run base gasoline. And this, in turn, can be used for operational control of the gasoline compounding process. This control can be carried out on the basis of the information received from capacitive sensors which are located in pipelines of the main material streams. Moreover, the control is carried out on the content of components (X, %) or on the value of the octane number (ON, point) of the mixture on the basis of experimentally obtained dependences 𝜀𝜀mix=𝑓𝑓(𝑋𝑋) and ОN=𝑓𝑓(𝜀𝜀mix).
Keywords: motor fuel; compounding; operational control; additives; dielectric constant; octane number; properties; gasoline